(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The first discovery of a Cretaceous pliosaurid tooth in Italy is reported. It comes from the Cenomanian-lower Campanian Argille Varicolori Formation near Castelvecchio di Prignano (Modena Province, northern Italy). Excepting this new specimen, Italy’s only reported pliosaurid is a humerus from the Upper Cretaceous of Zavattarello near Pavia. The tooth morphology allows it to be ascribed to Polyptychodon interruptus Owen, 1841, a species only reported thus far from northern-central Europe (England, Germany, and the Czech Republic). This suggests the presence of marine reptile remains in the northern Apennines may have been underestimated.